KELAYAKAN FINANSIAL USAHA TANI DAN PERSEPSI PETANI TERHADAP KEBIJAKAN KENAIKAN TARIF CUKAI HASIL TEMBAKAU (Studi Kasus di Kecamatan Suralaga Kabupaten Lombok Timur) - Dudi Septiadi; Rosmilawati Rosmilawati; Abdullah Usman; Asri Hidayati (Universitas Muhammadiyah Mataram, 2021)
Tobacco is a national strategic commodity that contributes to state revenues and employment. The purpose of this research is to analyze tobacco farming income and to analyze farmers' perceptions regarding the policy of increasing excise tariffs on processed tobacco/cigarette taxes. The research method used is qualitative analysis with a descriptive analysis approach. The research was conducted in Suralaga District, East Lombok Regency. Suralaga sub-district was chosen because it is a sub-district that mostly cultivates tobacco commodities. Respondents used in this study were 30 respondent farmers. 15 farmers live in Bagik Payung Village, some 15 farmers live in Waringin Village. Both villages are tobacco farmers and are located in Suralaga District, East Lombok Regency. The results showed that tobacco farming in East Lombok Regency was declared feasible because based on the analysis, the farming experienced an income (profit) of Rp. 8,045,942/hectare/planting season with a farming feasibility level of 1.70> 1 (feasible category). Most farmers have the perception that the policy of increasing tobacco excise/cigarette tax aims to help the national economy through increasing state revenues, not to control the level of cigarette consumption. The local/central government has never socialized the increase in tobacco/cigarette excise. In addition, farmers also assume that the government has never provided assistance or compensation to farmers after the policy of increasing tobacco/cigarette excise. The increase in cigarette excise does not have a direct impact on the decline in the economic condition of farmers. The factors that have the most direct influence on farmers' income are uncertain weather conditions (climate change) and the determination of the selling price grade of tobacco harvests which is less transparent.